Comparative evaluation of nutmeg mouthwash and 0.2% chlorhexidine gluconate mouthwash on halitosis and plaque control: A randomized clinical trial - Monika Vasantrao Padol; Prashanth Vishwakarma; Arun Suresh Dodamani; Anup Wamanrao Gore; Karina Shyamlal Chachlani; Shradha Pramod Kharkar (Wolters Kluwer Medknow Publications, 2022)
Background: Myristica fragrans, commonly known as nutmeg, has been shown to have many medicinal properties including reduction of plaque and oral halitosis. In the present study, a mouthwash was prepared from nutmeg oil to compare its effectiveness with 0.2% chlorhexidine (CHX) gluconate mouthwash on halitosis and plaque control. Materials and Methods: A total of 60 participants having plaque and plaque-induced oral halitosis were enrolled and randomly divided into two groups as Group A (30) and Group B (30). Nutmeg and 0.2% CHX gluconate mouthwash were administered in Group A and Group B, respectively, for 21 days twice daily. Plaque index and organoleptic score were recorded at baseline, 14th day, and 21st day. The data were collected, tabulated in Microsoft Excel Sheet, and subjected to statistical analysis using appropriate statistical tests. Results: The percentage of change in plaque score between baseline and 14th day was 12.3% and 9.44% (P = 0.741), between baseline and 21st day 39.2% and 39.4% (P = 0.889), and between 14th and 21st day 27.7% and 29.9% (P = 0.805) for Group A and Group B, respectively, while the percentage of change in halitosis score between baseline and 14th day was 24.7% and 16.3% (P = 0.201), between baseline and 21st day 54.5% and 56.3% (P = 0.487), and between 14th and 21st day 34.9% and 40.0% (P = 0.393) for Group A and Group B, respectively. Conclusion: Nutmeg mouthwash is organic, economical, and equally effective as compared to 0.2% CHX gluconate mouthwash (Clinical Trials Registry-India/2020/10/028540).